POLAR CONSTRUCTION EQUIPMENT UTILITY SERVICE SLED. - Gifford, S. E. (1963)
To facilitate construction and equipment operations in polar regions, a utility service sled was developed. It consists of a gasoline-enginedriven 8.75-kw electrical generator, a gasolineengine-driven 400,000-Btu/hr-output fresh-air heater, a 180-ampere arc welder, and a portable oxyacetylene cutting outfit mounted on a 1-1/2ton-capacity, two-section, fixed-runner cargo sled. The unit is suitable for tow with heavyduty personnel-type oversnow vehicles and Size 1 and 2 tractors. Use in field operations in Alaska and Antarctica showed the utility service sled to be an essential piece of support equipment for building construction, ice and snow runway construction, engine starting, and field repair of equipment in air temperatures down to -44 F. It was concluded that it should be adopted as a standard item for polar construction operations. (Author)